2021
DOI: 10.1016/j.pmedr.2021.101604
|View full text |Cite
|
Sign up to set email alerts
|

Firearm-related research articles in health sciences by funding status and type: A scoping review

Abstract: Highlights Federal restrictions have impacted funding for firearm-related research. We know little about the funding landscape for this research in the health sciences. A smaller proportion of articles reported funding in 2019 compared to 2000. Despite an increase in volume of publications, funding limitations still exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Although published empirical research on firearm injury has more than tripled since 2000, the amount of research as measured by the number of articles reporting funding is 30% lower in 2019 than in 2000 and only represents about 0.0006% of total published research in PubMed 65 . One reason for the limited research is that we have limited data with strong study designs, samples, and data collected.…”
Section: Future Directions For the Field Of Firearm Injury Preventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although published empirical research on firearm injury has more than tripled since 2000, the amount of research as measured by the number of articles reporting funding is 30% lower in 2019 than in 2000 and only represents about 0.0006% of total published research in PubMed 65 . One reason for the limited research is that we have limited data with strong study designs, samples, and data collected.…”
Section: Future Directions For the Field Of Firearm Injury Preventionmentioning
confidence: 99%
“…Even though funding for firearm injury prevention research and programming has been inadequate to address the burden of firearm injury and death, there have been some successes, including funding from private sources and increased federal funding in recent years. Local and state governments, foundations, and academic institutions have filled some of the deficit left by the decades of limited federal funding 65 . Gurrey and colleagues found that over 50% of firearm research publications published between January 2000 and December 2019 were funded by philanthropic sources 65 .…”
Section: Five Challenges and Successes In The Field Of Firearm Injury...mentioning
confidence: 99%
See 3 more Smart Citations